2020
DOI: 10.1016/j.msea.2020.139781
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature low cycle fatigue behavior of an equiatomic CoCrFeMnNi high-entropy alloy

Abstract: In the present work, low cycle fatigue (LCF) behavior of an equiatomic CoCrFeMnNi high entropy alloy (HEA) is correlated to the microstructural evolution at 550 °C. The fully reversed strain-controlled fatigue tests were conducted in air under strain amplitudes ranging from 0.2 to 0.8%. The measured cyclic stress response showed three distinct stages which include initial cyclic hardening followed by a quasi-stable cyclic response until failure. The rate and amount of cyclic hardening increased with the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 62 publications
(115 reference statements)
2
15
0
Order By: Relevance
“…Initially, grain-to-grain misorientations including plastic strain incompatibilities between grains, result in a significant increase in dislocation density close to the grain boundaries. Upon further cycling, as dislocations multiply and spread across grains, they interact (including activity of secondary slip) leading to cyclic hardening [14]. For CoCrNi, additional interactions between dislocations and SFs as well as SBs (that form concurrently) also contribute to the cyclic hardening.…”
Section: Fig 2e-f Provide Representative Overlaid Iq and Ipf Maps Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, grain-to-grain misorientations including plastic strain incompatibilities between grains, result in a significant increase in dislocation density close to the grain boundaries. Upon further cycling, as dislocations multiply and spread across grains, they interact (including activity of secondary slip) leading to cyclic hardening [14]. For CoCrNi, additional interactions between dislocations and SFs as well as SBs (that form concurrently) also contribute to the cyclic hardening.…”
Section: Fig 2e-f Provide Representative Overlaid Iq and Ipf Maps Of ...mentioning
confidence: 99%
“…However, engineering alloys are usually not only loaded monotonically in service but also cyclically. Few studies, concerning the fatigue properties of HEAs have been reported [14][15][16][17][18][19], where it was shown that CoCrFeMnNi demonstrates a higher low-cycle fatigue (LCF) resistance compared to common FCC steels [14,19]. Recently, Rackwitz et al [20] revealed a superior fatigue crack propagation resistance of CoCrNi compared to CoCrFeMnNi [21], especially at cryogenic temperatures, where the increased propensity of nanotwinning decreased the crack growth rate.…”
mentioning
confidence: 99%
“…
Fig. 5 Graphical compilation of low-cycle fatigue data of high-entropy alloys at the temperature of T = 298 K and strain ratio of R = −1 27 34 . ( a ) Total strain amplitude.
…”
Section: Technical Validationmentioning
confidence: 99%
“…Ten Cr x Mn 20 Fe 20 Co 20 Ni 40-x alloys ( x = 0, 5, 10, 14,16,18,20,22,24, and 26 at. %) were produced starting from pure elements (purity > 99.9 wt.%).…”
Section: Materials Processingmentioning
confidence: 99%
“…Due to its good malleability [13][14][15] , which made it the pioneering HEA to be thermomechanically processed and investigated in bulk form, and interesting mechanical properties at cryogenic temperatures, e.g. , excellent tensile properties [ 13 , 14 ], outstanding fracture toughness [2] , high resistance to lowcycle-fatigue [16][17][18] and fatigue crack propagation [ 19 , 20 ], it is one of the most studied HEAs of the last decade. The outstanding damage tolerance of the CrMnFeCoNi HEA is thought to result from its relatively low intrinsic stacking fault energy ( γ isf ≈ 30 mJ/m 2 , [ 21 , 22 ]) which promotes planar glide of dissociated dislocations [ 5 , 14 ], delays the onset of cross-slip [5] , and induces mechanical twinning [ 14 , 23 ], thereby resulting in sustained, high work hardening rate.…”
Section: Introductionmentioning
confidence: 99%